Influenza and pneumococcal vaccination in older adults living in nursing home: a survival analysis on the shelter study - Poscia, Andrea; Collamati, Agnese; Carfì, Angelo; Topinkova, Eva; Richter, Tomas; Denkinger, Michael; Pastorino, Roberta; Landi, Francesco; Ricciardi, Walter; Bernabei, Roberto; Onder, Graziano (European journal of public health, 2017)
BACKGROUND: Influenza and pneumococcal vaccines have been proved to be effective and safe in preventing and controlling infection among elderly, reducing morbidity and mortality. However, some evidences raised health concerns related to these vaccinations. This study aims to identify prevalence and outcomes related to influenza and pneumococcal vaccinations in a large European population of frail old people living in nursing homes (NHs). METHODS: We conducted a survival analysis of NH residents participating to the Services and Health for Elderly in Long-TERm project, a prospective cohort study collecting information on residents admitted to 57 NH in eight countries (Czech Republic, England, Finland, France, Germany, Italy, The Netherlands and Israel). Clinical and demographical data were collected using the international resident assessement instrument for long-term care facilities. Incident mortality was recorded during 1-year follow-up. A shared-frailty Cox regression model was used to assess the impact of vaccination status on mortality. RESULTS: Mean age of 3510 participants was 84.6 years (SD = 7.7). In total, 81.7 and 27.0% received influenza and pneumococcal vaccination, respectively. Overall, 727 (20.7%) residents died during the follow-up period. After adjusting for potential confounders, which included age, sex, number of diseases, depression, cognitive and functional status, influenza (HR = 0.80; 95% CI 0.66-0.97) and the combination of influenza and pneumococcal vaccination (HR = 0.72; 95% CI 0.57-0.91), but not pneumococcal vaccination alone (HR = 0.52; 95% CI 0.25-1.06), were associated with a statistically significant reduction in mortality in respect of no vaccinations. CONCLUSION: In a population of older adult living in NH influenza and the combination of influenza and pneumococcal vaccination were associated with a reduction in all-cause mortality respect to no vaccination.
Keywords: Europe; Female; Influenza Vaccines; Mortality; ženské pohlaví; Pneumococcal Vaccines; lidé; Survival Analysis; Evropa; Aged, 80 and over; mortalita; Frail Elderly; Nursing Homes; vakcíny proti chřipce; proporcionální rizikové modely; Male; křehký senior; pneumokokové vakcíny; analýza přežití; senioři nad 80 let; mužské pohlaví; Proportional Hazards Models; pečovatelské domovy; Humans